Alcohol consumption at age 11–12 years and traumatic dental injuries at age 15–16 years in school children from East London. Issue 5 (23rd February 2016) - Baig Enver, Muneera; Marcenes, Wagner; Stansfeld, Stephen A.; Bernabé, Eduardo
Abstract: Aim: To explore the association between alcohol consumption at age 11–12 years and traumatic dental injuries (TDI) at age 15–16 years. Methods: Data of 635 adolescents who participated in phases I and III of the Research with East London Adolescents Community Health Survey (RELACHS), a longitudinal school‐based survey of a representative sample of adolescents from East London, were used for this study. Information on socio‐demographic characteristics and alcohol consumption was obtained from questionnaires in phase I when adolescents were 11–12 years of age. Data on TDI and clinical characteristics (incisor overjet and lip coverage) were taken from clinical examination in phase III when adolescents were 15–16 years of age. The association between (lifetime and last month) alcohol consumption and TDI was assessed in crude and adjusted logistic regression models. Results: Overall, 14.5% of adolescents had ever consumed alcohol and 3.5% had consumed alcohol the month before the baseline survey, whereas 17% of adolescents had experienced TDI by age 15–16 years. No significant association of alcohol consumption with TDI was seen in these adolescents for either lifetime (adjusted odds ratio [OR]: 0.87; 95% confidence interval [CI]: 0.45–1.67) or last month consumption of alcohol (adjusted OR: 0.86; 95% CI: 0.28–2.69). Conclusion: This study did not support the association between alcohol use and TDI in adolescents.